Appearance of Five New Superior Varieties on Growth and Production of Rice - Sution, Sution (Faculty of Agriculture, Janabadra University, 2017)
This study aims to produce some new varieties of irrigated rice paddy field adaptive with good growth rate and high productivity. Implementation of research was in Bungkang Village, Sekayam Sub-district, in April until August 2015. Using Random Block Design consisting of five varieties, namely Inpari 10, Inpari 18, Inpari 19, Inpari 20, and Inpara 3, repeated five times. Cultivation technology used PTT approach, complete land management, fertilization based on PUTS, urea doses 150 kg ha-1, Kebomas NPK 15:15:15 200 kg ha-1, and SP-36 17 kg ha-1. Planting of legowo 4: 1 parallel system, age 18 dap, two to three seeds per hole, pest control with IPM principles. The observation result of the highest was Inpara 3 variety (114,77 cm), number of productive till at least 20 (12,92), longest shortest Inpara 2 and Inpari 20, respectively 24,32 cm and 24,82 cm. The highest number of grain contents and the highest number of panicles on Inpari 19 varieties were 94.58 grains and 119.32 grains respectively, while the highest vacuum percentage was Inpara 3, 23.26 percent. All Inpari varieties have 1000 grains weight higher than Inpara 3. The highest yield of grain harvest on Inpari 19 varieties, ie 8.55 t ha-1.Â Key-words: productivity, adaptive, irrigationÂ